Utility of Neck Circumference for Identifying Metabolic Syndrome by Different Definitions in Chinese Subjects over 50 Years Old: A Community-Based Study - Shuo Lin; Li Hu; Ping Li; Xiaofeng Li; Keyi Lin; Bilian Zhu; Panwei Mu; Longyi Zeng (Journal of Diabetes Research)
Aims. Whether neck circumference (NC) could be used as a valuable tool for identifying metabolic syndrome (MS) by different criteria in Chinese is still unclear. Methods. We conducted a cross-sectional survey from October 2010 to January 2011 in Shipai community, Guangzhou, Guangdong Province, China. A total of 1473 subjects aged over 50 years were investigated. We measured height, weight, NC, waist circumference, blood pressure, blood glucose, and lipids in all subjects. MS was identified by criteria of the National Cholesterol Education Program-Adult Treatment Panel III (NCEP-ATP III), Chinese Diabetes Society (CDS), and International Diabetes Federation (IDF). Results. Mean NC was 38.0 ± 2.7 cm in men and 34.2 ± 2.5 cm in women. By using receiver operating characteristic curves, the area under the curve (AUC) of NC for identifying MS (IDF) was 0.823 in men and 0.777 in women, while for identifying MS (CDS), it was 0.788 in men and 0.762 in women. The AUC of NC for diagnosing MS (ATP III) was 0.776 in men and 0.752 in women. The optimal cut points of NC for MS were 38.5 cm by three definitions in men, while those were 34.2 cm, 33.4 cm, and 34.0 cm in women by IDF, ATP III, and CDS definitions, respectively. No significant difference was observed between the AUC of NC and BMI for diagnosing MS by using different criteria (all p>0.05). Conclusions. NC is associated with MS by different definitions in Chinese subjects over 50 years old. It may be a useful tool to identify MS in a community population.